(untitled) (Marketing Journal, 2025)
The article examines the experience of developed countries in improving the activities of small and medium -sized businesses through financial and credit mechanisms, and analyzes the trends in its development. It also explains the essence of the measures pl anned for further implementation to stimulate the activities of small and medium -sized businesses through financial and credit mechanisms.